Can digital finance promote low-carbon transition? Evidence from China - GE, Xing (Institutional Knowledge at Singapore Management University, 2023)
Using panel data of Chinese cities from 2011 to 2019, this paper analyzes the impact of digital finance on low-carbon transition derived from a super-efficiency slacks-based measure data envelopment analysis. We find that digital finance promotes low-carbon transition, and this finding is robust with respect to the choice of sample, potential presence of measurement issue, choice of study period, presence of other policies, and potential endogeneity, among others. This impact is at least in part goes through increased green innovations. We also find evidence for impact heterogeneity across locations and by the level of low-carbon transition.